Music in the home - Smith, Sallie Maud (My University, 1904)
Introduction: Music is the art which employs sound as a medium of artistic expression for what is not in the province of literature of sculpture painting of acting or archuitecture. Music embodies the inward feelings of which all other arts can but exhibit the effect. Music is inexpressive, but is one of the qualities that place it on the highest level of art excellence and to have a marked influence on the literature as well as benefitting the player. Music has a higher mission than merely to please the ear. It is the art which appeals to the heart which must affect our character. On how many wearied marches have the songs been a means of cheer. How often have they inspired the fighting soldier when almost ready to give up in the face of overpowering forces?
Citation: Smith, Sallie Maud. Music in the home. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Music; Home Living; Effects of Music; Music at Home; Theses; Manuscripts (documents)